On The Problem Of Loan Terms In Kazakh Terminology - Mazhitaeva, S.M.; Rapisheva, Z.; Khan, N.; Ayazbaeva, B.; Rahymberlina, S.; Abduyov, М. (Marsland Press / Zhengzhou University, 2014)
Terminology is the means of information exchange, a tool in mastering specialty, important factor of communication between people as a way accelerating technical progress. The given article analyzes experiences of accepting international terms common to several languages by other languages. Authors of the article clearly show on the material of examples certain degree of modern international term formation, usage of Kazakh words in their translation, peculiarities of the usage of Arabic, Persian and Russian terms. The aim of the present article is to point on the principles, ways and methods through which loan terms and international terms are given in Kazakh language, define capability of Kazakh language in translating international terms.
Keywords: term; terminological lexis; loan term; international term; state language; translation; ormation; stabilization